Pengaruh Pemberian Ekstrak Bunga Pepaya (Carica papaya L.) terhadap Gambaran Histopatologik Aorta Tikus Wistar (Rattus norvegicus) yang Diinduksi Diet Tinggi Lemak - Suci Apriani Ponamon; Maria Kristanti Sambuaga; Carla Felly Kairupan (Pusat riset dan Inovasi Nasional, 2026)
A high-fat diet can cause hyperlipidemia, which is one of the main risk factors for atherosclerosis. Papaya flowers (Carica papaya L.) contain antioxidants that have the potential to inhibit the development of atherosclerotic lesions. This study aims to determine the effect of papaya flower extract on the histopathological features of the aorta of Wistar rats induced by a high-fat diet. The study design is a posttest only-trial group design. The study sample consisted of 25 male Wistar rats divided into 5 groups with treatment for 21 days. Group A received no treatment. Group B was given high-fat diet consisting of 3 mL of pork fat and 2 g of duck egg yolk. Group C was given high-fat diet and simvastatin 0.18 mg/200 gBW. Groups D and E were given high-fat diet and papaya flower extract 125 mg/kgBW and 250 mg/kgBW, respectively. The parameter used is the histopathological description of the aorta in the form of foam cell formation. The results showed that there were few foam cell in group A. Group B had many foam cells in the tunica intima and media of aorta. Group C, D and E showed a reduction in the number of foam cells. The administration of papaya flower extract (Carica papaya L.) was effective in inhibiting foam cell formation in the aorta of Wistar rats induced by a high-fat diet, with a better effect seen at a dose of 250 mg/kgBW, which was almost comparable to simvastatin.